Current loot box warnings are ineffective for informing consumers. (February 2023) - Garrett, Eamon Patrick; Drummond, Aaron; Lowe-Calverley, Emily; Sauer, James D.
Abstract: Loot boxes - a form of in-game purchase within video games (i.e., "microtransactions") - have received research attention due to their similarities with conventional gambling activities. A consistent positive correlation has been demonstrated between spending on loot boxes and problem gambling symptomatology. In April 2020, the video game regulatory boards across the United States (ESRB) and Europe (PEGI) announced a new warning label would be implemented for games than include loot boxes: "In-Game Purchases (Includes Random Items)". Such warnings may mitigate spending-related harms to consumers if they effectively inform consumers' spending decisions. Here, we summarise findings from three preregistered studies showing that (1) consumers perceive that engaging with loot boxes has a potential for harm greater than non-randomised microtransactions, but lower than most gambling activities, (2) the perception of harm inferred by consumers from existing warning labels does not align closely to the potential harms perceived to be associated with loot box engagement, and, perhaps most importantly, (3) consumers do not appear to understand the ESRB/PEGI loot box warning. Thus, current warnings may fail to adequately inform consumer spending decisions. Highlights: ESRB/PEGI loot box warning is poorly comprehended. Most participants fail to identify the chance element of the warning. Loot boxes perceived as higher in potential harm than non-random microtransactions. Loot boxes perceived as lower in potential harm than conventional gambling activities. Perceptions of harm for purchasing loot boxes and loot box warnings not commensurate.